The Effect of Trustworthiness to Increase Brand Trust and Purchase Intention on Social Media Promotion based on Theory of Persuasion in Generation Z - Rizma, Febrita Aulia; Marsasi, Endy Gunanto (Jurnal Manajemen, 2024)
This study aims to examine social media users against the background that the concept of trustworthiness has not been optimized to increase brand trust and purchase intention on social media promotions among generation Z. Trustworthiness positively influences purchase intention, indicating that feeling confident in brand trust and trustworthiness, amak is inclined to make purchase intentions for the promoted product or service. Persuasion Theory is an approach that aims to change a person's beliefs and ways of thinking through strong and effective arguments. The research method uses quantitative with purposive sampling technique and uses 225 respondents to be tested Structural Equation Modeling (SEM) analysis was conducted using IBM SPSS Statistic 27 and SEM AMOS24. The main research results show that all hypotheses have a significant positive relationship. New findings in this study show that social attractiveness has a significant negative relationship with parasocial relationships. The results explain that trust can increase brand trust and purchase intention on social media promotions. This research can provide assistance to companies regarding factors that can create purchase intentions for promotions on social media. This study has an update on the variables, namely the addition of brand trust variables to increase purchase intention.